Performance evaluation of carbide tool in end milling of medium density fiberboard - Yusoff, Salahuddin (2010)
The purpose of this study is to investigate the performance evaluation of carbide tool in end milling rubber MDF board. A series of cutting tests were carried out to evaluate the tool wear, surface finish, and chip formation of the workpiece with respect to the increase of cutting distance. Cutting tests were performed under various combinations of spindle speeds (10000, 12000 and 15000 rpm) and feed per tooth (0.20 and 0.25 mm/tooth). The cutting forces were measured at initial cutting using tool force dynamometer and were recorded using a multi component force measuring system.